Türkiye Büyük Millet Meclisi tutanaklarında Türk-Yunan ilişkileri ve “Avrupalılaşma” : 1994-2006 = Relations between Turkey & Greece and “Europeanization”, a survey based on official records of Turkish Grand National Assembly : 1994-2006 - Erdoğan, M. Murat. (Ankara)
97, 96 s.